MOF@wood Derived Ultrathin Carbon Composite Film for Electromagnetic Interference Shielding with Effective Absorption and Electrothermal Management - Ma, Xiaofan; Liu, Siyuan; Luo, Heng; Guo, Hongtao; Jiang, Shaohua; Duan, Gaigai; Zhang, Guoying; Han, Jingquan; He, Shuijian; Lu, Wei; Zhang, Kai (Advanced functional materials, 2024)
Recently, there has been a growing demand for ultra‐thin carbonized wood films (CWF) with high shielding efficiency (SE) to replace non‐renewable alternatives. Researchers aim to enhance electromagnetic (EM) wave absorption and improve electromagnetic interference (EMI) SE in CWF materials to reduce secondary pollution from reflected EM waves. In this work, the carbonized wood composite film (CWF/EP/Co) with a thickness of 120 µm through the process of hot‐pressing and carbonizing wood soaked in a mixed solution of water‐borne epoxy (EP) and Co/Zn‐MOF (ZIF‐67/8) is obtained. The CWF/EP/Co film exhibits excellent conductivity (105 S cm−1) and demonstrates an excellent EMI SE (73 dB) at a 200 µm thickness. Remarkably, the specific EMI shielding effectiveness (SSE/t) of CWF/EP/Co films reached 15833.3 dB·cm2·g−1 in the X‐band, making it the highest reported value among all wood‐derived EMI shielding materials. CWF/EP/Co films have a high absorption coefficient (A) of 0.4, indicating their effectiveness in absorbing EM waves. Furthermore, the EMI shielding effect of the large‐scale wallpaper (170 mm×170 mm) is confirmed by finite element analysis. Additionally, the CWF/EP/Co film exhibits good mechanical properties and effective Joule heating performance. This shielding film shows promise in applications such as buildings and smart homes, providing EMI shielding and warming effects. This work reports ultra‐thin CWF/EP/Co films (120 µm) by a simple two‐step method of hot‐pressing and carbonization. It demonstrates an impressive EMI SE (73 dB) at a 200 µm thickness. The specific EMI shielding effectiveness (SSE/t) of CWF/EP/Co films reaches 15 833.3 dB·cm2·g−1, much higher than other wood‐based materials. Moreover, CWF/EP/Co films exhibit favorable EM absorbing properties and effective Joule heating performance.